Data of the natural and pharmaceutical angiotensin-converting enzyme inhibitor isoleucine-tryptophan as a potent blocker of matrix metalloproteinase-2 expression in rat aorta - Kopaliani, Irakli (Data Brief, 2016)
The present data are related to the research article entitled “Whey peptide isoleucine–tryptophan inhibits expression and activity of matrix metalloproteinase-2 in rat aorta” [1]. Here we present data on removal of endothelium from aorta, endothelium dependent aortic relaxation and inhibition of expression of pro-MMP2 by di-peptide isoleucine–tryptophan (IW). Experiments were performed in rat aortic endothelial cells (EC) and smooth muscle cells (SMC) in vitro, along with isolated rat aorta ex vivo. The cells and isolated aorta were stimulated with angiotensin II (ANGII) or angiotensin I (ANGI). ACE activity was inhibited by treatment with either IW or captopril (CA). Losartan was used as a blocker of angiotensin type-1 receptor. IW inhibited MMP2 protein expression induced with ANGI in a dose-dependent manner. IW was effective both in ECs and SMCs, as well as in isolated aorta. Similarly, captopril (CA) inhibited ANGI-induced MMP2 protein expression in both in vitro and ex vivo. Neither IW nor CA inhibited ANGII-induced MMP2 protein expression in contrast to losartan. The data also displays that removal of endothelium in isolated rat aorta abolished the endothelium-dependent relaxation induced with acetylcholine. However, SMC-dependent relaxation induced with sodium nitroprusside remained intact. Finally, the data provides histological evidence of selective removal of endothelial cells from aorta.